2017
DOI: 10.17996/anc.17-00015
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Assessments of Cardiac Sarcoidosis Using <sup>18</sup>F-FDG PET

Abstract: Sarcoidosis is a multisystem disease pathologically characterized by non-caseating granuloma. Cardiac sarcoidosis (CS) remains an important prognostic factor of sarcoidosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…Sarcoidosis is a multisystem disease pathologically characterized by non-caseating granuloma [ 1 6 ]. Cardiac sarcoidosis (CS) occasionally causes cardiac death via congestive heart failure, ventricular tachyarrhythmia, and advanced conduction disturbance [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcoidosis is a multisystem disease pathologically characterized by non-caseating granuloma [ 1 6 ]. Cardiac sarcoidosis (CS) occasionally causes cardiac death via congestive heart failure, ventricular tachyarrhythmia, and advanced conduction disturbance [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 F-Fluorodeoxyglucose (FDG) is widely used as a positron emission tomography (PET) tracer to assess malignant and active inflammatory diseases. The main advantage of FDG PET is its ability to visualize metabolic activity to complement anatomic imaging [ 6 , 7 ]. Previous studies have demonstrated the usefulness of FDG PET in diagnosing CS and monitoring treatment response [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study, we analyzed patients who underwent 18 F-FDG PET/CT and were diagnosed as having CS based on the Japanese Society of Sarcoidosis and Other Granulomatous disorders (JSSOG) guidelines [22] during the period from May 2010 to April 2017. Thirty-three CS patients who did not receive oral steroid treatment before 18 F-FDG PET/CT were allocated to a CS group.…”
Section: Study Subjectsmentioning
confidence: 99%
“…In this retrospective study, we analyzed patients who underwent 18 F-FDG PET/CT and were diagnosed as having CS based on the Japanese Society of Sarcoidosis and Other Granulomatous disorders (JSSOG) guidelines [22] during the period from May 2010 to April 2017. Thirty-three CS patients who did not receive oral steroid treatment before 18 F-FDG PET/CT were allocated to a CS group.…”
Section: Study Subjectsmentioning
confidence: 99%